Kejadian Luar Biasa (KLB) Difteri di Provinsi Jawa Timur Tahun 2013-2015: Tinjauan Histori Epidemiologi - Lymbran Tina; Satriani Satriani; Adinda Lestari Febrianti; Angela Anastasya Anggau (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Diphtheria remains a public health concern and has the potential to cause outbreaks. East Java Province is one of the regions in Indonesia with a high burden of diphtheria cases and a history of recurrent outbreaks. This study aimed to describe the epidemiology of diphtheria outbreaks in East Java Province during 2013-2015 based on person, place, and time distribution and to identify factors associated with their occurrence. This study employed a descriptive design using a secondary data analysis and literature review approach. Data were obtained from official reports of the East Java Provincial Health Office, publications of the Ministry of Health of the Republic of Indonesia, and relevant scientific articles. The results showed that diphtheria outbreaks predominantly occurred among individuals aged ≤15 years (43 cases) and those without a history of immunization (13 cases). Blitar Regency recorded the highest number of cases (38 cases), while the peak incidence occurred in April (13 cases). Factors associated with the outbreaks included incomplete immunization, low public knowledge, unhealthy environmental conditions, and suboptimal surveillance systems. Post-outbreak trends indicated that diphtheria remains a significant public health problem, with the case fatality rate (CFR) reaching 56.25% in 2024. Therefore, strengthening immunization coverage, epidemiological surveillance, early case detection, and clinical case management is essential to reduce diphtheria-related morbidity and mortality in East Java Province.